FUNGSI & MAKNA BANTEN PRAYASCITA DI KOTA DENPASAR - Ni Ketut Sukiani (Universitas Warmadewa, 2019)
[Title : The Function and Purpose of Banten Prayascita at Denpasar] The Hindu people in Bali is well acquainted with variations found in yadnya which adapted to its degree. But unfortunately not many people who understand about the function and meaning of banten, especially the Banten Prayascita. This aim of this study is to increase the understanding of the function and the meaning of Banten Prayascita in Yadnya. The data in this study were obtained from literature review and interviews from the banten professionals. The research method using a qualitative approach that emphasizes the integrity of a cultural phenomenon. Banten Prayascita is a set of banten that has the core function of sanctification and each component of the banten has its own meaning that form a unity to invoke the purification to Ida Sang Hyang Widhi Wasa. Banten Prayascita has a special role and is very often used in the implementation of yadnya.